Empirical cloud security - Sood, Aditya (Duxbury : Mercury Learning and Information, 2023)
"This updated edition is designed for security and risk assessment professionals, DevOps engineers, penetration testers, cloud security engineers, and cloud software developers who are interested in learning practical approaches to cloud security. It covers practical strategies for assessing the security and privacy of your cloud infrastructure and applications and shows how to make your cloud infrastructure secure to combat threats, attacks, and prevent data breaches. The chapters are designed with a granular framework, starting with the security concepts, followed by hand-on assessment techniques based on real-world studies, and concluding with recommendations including best practices"--